Creative Content Development and Tourism Village Website Management Training to Increase Tourist Visits: A Community Engagement Program in Bukit Lawang - Metta Dina Gloria; Irwan Jani Tarigan; Anzas Ibezato Zalukhu; Tomy Satria Alasi; Marwa Halim; Riandy Yap; Ramen A Purba; Adil Priman Hati Hulu; Dahrim; Suhendri Nasution (Jurnal Pengabdian Masyarakat Variasi, 2026)
Bukit Lawang is one of the leading ecotourism destinations in North Sumatra, renowned for its Orangutan conservation and the natural beauty of Gunung Leuser National Park. However, this great potential has not been accompanied by independent digital promotion optimization by the local community. Most tourism stakeholders still rely on third parties (external travel agents) and have not maximized the use of the village's digital assets. This Community Service activity (PKM) aims to improve the skills of the Tourism Awareness Group (Pokdarwis) and local youth in creative content creation (photo/video) and management of the official tourism village website. The implementation method uses the Asset-Based Community Development (ABCD) approach divided into a preparation stage, implementation stage (theoretical and practical training), and evaluation stage using pre-test and post-test questionnaires analyzed with the Normalized Gain (N-Gain) test and the non-parametric Wilcoxon Signed-Rank Test. Results show a significant increase in partner understanding, with a “High” N-Gain category across all indicators: 0.77 in photography/videography techniques, 0.75 in video editing skills via smartphone, and 0.72 in website dashboard operational capabilities. A Wilcoxon Signed-Rank Test confirmed that the increase from pre-test to post-test (mean 54.88 to 78.72) was statistically significant (Z = -4.478; p < 0.001). The long-term impact is the availability of independently managed digital promotional media to attract both domestic and international tourist visits directly without intermediaries